Smoothie Drinks: Possible Source of Resistant and Biofilm-Forming Microorganisms - Šilha, David; Syrová, Petra; Syrová, Lenka; Janečková, Jana (Foods, 2022)
Smoothie drinks are currently very popular drinks sold especially in fast food establishments. However, smoothies are a significant source of microorganisms. The aim of this study was to evaluate the microbiological quality of smoothies purchased in Eastern Bohemia. A higher prevalence of mesophilic aerobic bacteria (5.4-7.2 log CFU/mL), yeast (4.4-5.9 log CFU/mL) and coliform bacteria (3.1-6.0 log CFU/mL) was observed in vegetable smoothies, in which even the occurrence of enterococci (1.6-3.3 log CFU/mL) was observed. However, the occurrence of S. aureus, Salmonella spp. and Listeria spp. was not observed in any samples. Nevertheless, antimicrobial resistance was observed in 71.8% of the isolated strains. The highest level of resistance was found in isolates from smoothie drinks with predominantly vegetable contents (green smoothie drinks). Considerable resistance was observed in Gram-negative rods, especially to amoxicillin (82.2%) and amoxicillin with clavulanic acid (55.6%). Among enterococci, only one vancomycin-resistant strain was detected. The vast majority of isolated strains were able to form biofilms at a significant level, which increases the clinical importance of these microorganisms. The highest biofilm production was found in Pseudomonas aeruginosa, Kocuria kristinae and Klebsiella pneumoniae. Overall, significant biofilm production was also noted among isolates of Candida spp.